Elements of Discrete Mathematics - Liu, C. L.; Mohapatra, D. P. (New Delhi: TMH, 1985)
Elements of Discrete Mathematics is a comprehensive book undergraduate students of Computer Science Engineering. The book comprises chapters on sets and permutations, permutations, combinations and discrete probability, relations and functions, graphs and planar graphs, modeling computation, analysis of algorithms and recurrence relations and recursive algorithms. In addition, the book consists of several solved examples, practice problems, illustrations and algorithms to understand the concepts better. This book is essential for candidates preparing for various competitive examinations like GATE and IES.
Index 617-627p.; Reprint 2013.
Keywords: Boolean algebras; Recurrence relations; Modeling computation